Membangun Bisnis Digital melalui Project-Based Learning: Studi Pengembangan Website Pemesanan Online siMenu - Syifa Nursaadah; Ferrol Azki Mashudi; Ester Olivia Silalahi; Wien Kuntari (Switch : Jurnal Sains dan Teknologi Informasi, 2025)
In the current digital era, SMEs in the culinary sector face challenges in adopting technology to improve operational efficiency. One solution to address this issue is the use of a simple and cost-effective QR Code-based application. This study aims to develop and implement siMenu, an application that provides table, order, and product management solutions without integrating complex digital payment systems. The method used is Project-Based Learning (PBL), which allows the development of technical skills while designing a sustainable business model through Business Model Canvas (BMC). The results show that siMenu successfully improved operational efficiency for SMEs, reduced ordering errors, and provided an easy-to-adopt solution with low implementation costs. However, challenges in application development and building user trust remain obstacles. The conclusion of this study is that simple digital solutions like siMenu can help SMEs in the culinary sector digitally transform and stay competitive in an increasingly evolving market.